Cell-cell adhesion mediated by binding of membrane-anchored transforming growth factor alpha to epidermal growth factor receptors promotes cell proliferation. - Anklesaria, P (1990)
The precursor for transforming growth factor alpha, pro-TGF-alpha, is a cell surface glycoprotein that can establish contact with epidermal growth factor (EGF) receptors on adjacent cells. To examine whether the pro-TGF-alpha/EGF receptor pair can simultaneously mediate cell adhesion and promote cell proliferation, we have expressed pro-TGF-alpha in a bone marrow stromal cell line. Expression of pro-TGF-alpha allows these cells to support long-term attachment of an EGF/interleukin-3-dependent hematopoietic progenitor cell line that expresses EGF receptors but is unable to adhere to normal stroma. This interaction is inhibited by soluble EGF receptor ligands. Further, the hematopoietic progenitor cells replicate their DNA while they are attached to the stromal cell layer and become foci of sustained cell proliferation. Thus, pro-TGF-alpha and the EGF receptor can function as mediators of intercellular adhesion and this interaction may promote a mitogenic response. We propose the term "juxtacrine" to designate this form of stimulation between adjacent cells.